Bifurcation picture and stability of the gap and out-gap discrete solitons - Kroon, L.; Bogdan, M.M.; Kovalev, A.S.; Malyuta, E.Yu. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The dynamics of a quaternary fragment of a discrete system of coupled nonlinear oscillators with modulated frequency parameters is investigated and the stability of its gap and out-gap soliton-like excitations is studied.